The Doctrine of Humanity in the Theology of Reinhold Niebuhr - Hamilton, Kenneth (Book collections on Project MUSE., 2013)
Reinhold Niebuhr was a twentieth-century American theologian who was known for his commentary on public affairs. One of his most influential ideas was the relating of his Christian faith to realism rather than idealism in foreign affairs. This title exposes not only the internal consistency of Niebuhr's project but also its aporia.